Pengembangan Media Big Book Game Running Story untuk Meningkatkan Minat Membaca Peserta didik Kelas V Sekolah Dasar - Pandan Sari, Wuni; Gamaliel Septian Airlanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop the Big Book Game Running Story media as a learning tool that can increase reading interest in fifth grade elementary school students. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research results show that this media is very valid according to the assessment of media experts (95%), valid by material experts (79%), and language experts (75%). The effectiveness test shows a significant increase between the pretest and posttest scores. The practicality of this media is also rated very high based on responses from teachers (90%) and students (85.8%). Thus, the Big Book Game Running Story is suitable for use as an Indonesian language learning medium to increase students' interest in reading. Keywords: Big Book, Running Story Game, Interest in Reading